Effect of gardening on the human psychological and physiological state - TARAN, Natalya; BATSMANOVA, Lyudmila; KOSYK, Oksana; ZYMA, Igor (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The impact of gardening on brain function and emotions is presented in this review of the scientific literature. Informational and emotional tension and overload are constantly experienced in today's people's lives, and it can lead to anxiety and discomfort. Maintaining the mental health of adults and children is one of the most critical tasks because everyone's quality of life and personal development depends on it. Human interaction with plants reduces anxiety and stress. Therefore, the study aimed to determine the influence of certain types of gardening activities on the psychophysiological functions of the human brain.Results. Scientific studies have confirmed that gardening (plant care, contact with the soil) has many physical and mental benefits for recovery and elimination of the effects of psycho-emotional overstrain of modern man. A natural, green environment reduces stress, while an urban environment has the opposite effect. Due to the positive results of gardening, retirement homes offer this type of activity to middle-aged and elderly people, office workers, and the general public to reduce stress and increase positive emotions. Thanks to the rapid development of neuroscience, emotional processes in the brain can be assessed with the help of neuroimaging. In particular, functional magnetic resonance imaging (fMRI) and a profile of mood states can be used to determine physiological and psychological indicators. It is shown that the functional connectivity of activated parts of the brain is formed after each gardening activity. Thus, at the stage of plot preparation and sowing, examined persons concentrated on the mechanical cultivation of the soil, which made it easier for them to enter a stage of focused awareness similar to meditation on perception. The novelty of gardening skills evokes creativity and belongs to the emotional processing and prosodic network.Conclusions. Gardening work (sowing seeds, planting seedlings, applying fertilizers, weeding, etc.) stabilizes a person's psychoemotional state. Gardening strengthens the formation of functional connections in the brain lobes, including the emotional prosody network (promoting positive thinking, emotional regulation, self-control, and creative thinking). This information can be used to develop therapy methods for people with special needs, considering specific types of gardening activities.
Keywords: gardening; psychological and emotional state; parts of the brain; functional brain activity; emotions; functional connections; brain lobes; prosodic network; functional magnetic resonance imaging; profile of mood states